PENGEMBANGAN MEDIA KERETA PINTAR UNTUK MENGENAL KONSEP LAMBANG HURUF ANAK USIA 4-5 TAHUN - Lestari Aprilianti; Sri Widayati (JURNAL LENTERA ANAK, 2021)
During the golden age, children need to be stimulated according to their age and ability, one way that can be done is by using the media. The purpose of this study is to develop a feasible, practical and effective smart train media to recognize the concept of letter symbols for children aged 4-5 years. The research method used is a 4D research type developed by Thiagarajan, namely define, design, develop and disseminate. The subjects in this study were 1 material expert and media expert, 10 children aged 4-5 years and 5 kindergarten teachers. The data collection technique in this study used a questionnaire and non-participant observation with a limited trial. The data analysis technique carried out by the researcher used qualitative data and quantitative data. The result of this research is to get a percentage of 96.4% from material experts and 95% from media experts. The percentage results from student responses are 93% and from teacher responses are 92%. Analysis of the calculation results from the observation sheet on the subject of a limited trial, namely t count of -10,585 with a significant value (2-tailed) of 0.000 which is smaller than 0.05, it can be concluded that the smart train media is feasible, practical and effective to recognize the concept symbols for children aged 4-5 years.